EFFECTIVE CRISIS MANAGEMENT FOR ISLAMIC FINANCIAL INDUSTRY AND THE INSTITUTION OF HISBAH: LESSONS FROM GLOBAL FINANCIAL CRISIS - Najeeb Zada; Ahcene Lahsasna; Muhammad Yusuf Saleem (Share: Jurnal Ekonomi dan Keuangan Islam, 2016)
The recent financial crisis resulted destructive effects on finance industry. Islamic financial industry (IFI) is still naÃ¯ve and largely untested in the face of a major financial turmoil. Major issues and uncertainties of the insolvency of IFI include the issue of moral hazard, government bailouts, excessive risk taking and deposit insurance. This paper addresses the issue of crisis management in IFI from the perspective of al-Siyasah al-Sharâ€™iyyah and attempts to derive public policy guidelines that are useful in developing a timely and efficient crises management framework for Islamic finance industry. By using qualitative methods, the study found that the global financial crisis resulted in great destruction of financial institution. Although Islamic finance was quite immune to the global crisis as compared to its conventional peer, concerns still exist. It is time that Islamic finance industry learns from the financial woes of the rest of the world. =========================================== Krisis keuangan baru-baru ini mengakibatkan efek destruktif pada industri keuangan. Industri keuangan Islam (IKI) masih naif dan sebagian besar belum teruji dalam menghadapi gejolak keuangan besar. Isu utama dan ketidakpastian dari kebangkrutan IKI meliputi moral hazard, dana talangan pemerintah, pengambilan risiko yang berlebihan dan asuransi deposito. Makalah ini membahas isu manajemen krisis dalam IKI dari perspektif al-Siyasah al-Shar'iyyah dan berusaha mendapatkan pedoman kebijakan publik yang bermanfaat dalam mengembangkan kerangka kerja manajemen krisis yang tepat waktu dan efisien bagi IKI. Dengan menggunakan metode kualitatif, studi ini menemukan bahwa krisis keuangan global mengakibatkan kehancuran besar bagi industri keuangan. Meskipun keuangan Islam cukup kebal terhadap krisis global dibandingkan dengan keuangan konvensional, kekhawatiran masih ada. Sudah saatnya industri keuangan Islam belajar dari krisis keuangan dari seluruh dunia.